Narrative as an approach in teacher preparation programme - Saharuddin, Norzihani; Hussien, Suhailah; Abdullah, Nur Surayyah Madhubala; Yasin, Maizura (Horizon Research Publishing, 2020)
This study explored the experience of preservice teachers in a coursework that was instructed using the Narrative Approach in University Putra Malaysia. In doing so, the study intended to examine the perceptions of the preservice teachers about learning in a Narrative Approach classroom. This study is a case study of six preservice teachers in their sixth semester of the Teacher Education Programme in UPM. The main data collection technique was semi-structured interview with the six preservice teachers and triangulation with the researcher's class observation and semi-structured interview with the LHE 3313's (Moral Issues and Conflicts). The data were transcribed, analysed and the emerging themes were categorised and discussed. The findings revealed that the preservice teachers generally had mixed perceptions including pleasant and unpleasant experiences towards learning using the Narrative Approach. This study has crucial implications for Moral Education instructors and curriculum developer in creating a more effective and successful teaching approach of the courses especially for preservice teachers.